CORPORATE ATTRIBUTES AND BANKRUPTCY PREDICTION: THE CASE OF LISTED HALAL FOOD AND BEVERAGE COMPANIES - Umar, Umar Habibu; Abduh, Muhamad; Besar, Mohd Hairul Azrin (Bank Indonesia, 2024)
This study investigates the relationship between corporate attributes and the probability of bankruptcy among halal food and beverage companies in five countries: Indonesia, Malaysia, Pakistan, Saudi Arabia, and the United Arab Emirates (UAE). Analyzing data from 56 firms from 2008 to 2021 using static panel data method, we find that the working capital period (cash conversion cycle), leverage, and firm growth increase the probability of bankruptcy for these companies. In contrast, liquidity, profitability, and firm size reduce bankruptcy probability. The findings reveal essential firm attributes that can guide the management of halal food and beverage firms, relevant regulators, and potential investors in ensuring the firms’ long-term viability.